2014
DOI: 10.1108/maj-05-2013-0862
|View full text |Cite
|
Sign up to set email alerts
|

Leaving a joint audit system: conditional fee reductions

Abstract: Purpose – The authors aim to exploit a natural experiment in which voluntary replace mandatory joint audits for Danish listed companies and analyse audit fee implications of using one or two audit firms. Design/methodology/approach – Regression analysis is used. The authors apply both a core audit fee determinants model and an audit fee change model and include interaction terms. Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 26 publications
1
31
0
Order By: Relevance
“…Empirical evidence on audit fee differences between single and joint audits is scarce (Zerni et al ., ; Holm & Thinggaard, ; André et al ., ). Similar to this study, Holm and Thinggaard () analyse audit fees in the first years after the abolition of the Danish mandatory joint audit system. They examine the full population of non‐financial listed companies and apply both a core audit fee determinants model and an audit fee change model.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical evidence on audit fee differences between single and joint audits is scarce (Zerni et al ., ; Holm & Thinggaard, ; André et al ., ). Similar to this study, Holm and Thinggaard () analyse audit fees in the first years after the abolition of the Danish mandatory joint audit system. They examine the full population of non‐financial listed companies and apply both a core audit fee determinants model and an audit fee change model.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…But the absence of single audit cases makes France an unsuitable subject for an empirical test of single versus joint audits. Mandatory joint audits were required for listed companies in Denmark from 1930 to 2004, but the provision was abolished for the auditing of financial reports after 1 January 2005 (Holm & Thinggaard, ). The Danish change in 2005 from a mandatory to a voluntary joint system led to statutory audits conducted as single audits or joint audits.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, 45 financial companies were excluded since their operations and financial statements differed substantially from those of the majority of the other listed companies (Gonthier‐Besacier & Schatt, ). Nonfinancial companies are commonly used within audit fee research, and this is also applicable in previous studies conducted in a Nordic context (Holm & Thinggaard, ; Niemi, ). A further 11 companies were excluded due to lack of data, leaving 197 companies for inclusion in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Two meta-analyses (Hay, 2013;Hay et al, 2006) have shown convincing results indicating that client size is the most important determinant of audit fees. The size of the company was operationalized by using the natural logarithm of total assets at yearend (ASSETS) (Firth, 1997;Holm & Thinggaard, 2014;Niemi, 2002).…”
Section: Control Variablesmentioning
confidence: 99%
“…Under this system, at least one of the auditors had to be a state authorised auditor. 1 The joint audit provision remained in force in Denmark until 1 January 2005 (see Holm and Thinggaard, 2014). In 1931, the 1930 Act was repealed and its provisions were incorporated in a new Business Act (Act No.…”
Section: Statute Law On the Role And Responsibilities Of The Auditormentioning
confidence: 99%